THE COGNITIVE IMPPAIRMENT AND ITS RELATED FACTORS AMONG FACTORS AMONG ELDERLY HYPERTENSIVE IN TWO RURAL DISTRICTS AREAS, MALAYSIA - Mohamad Rodi Isa; Siti Munira Yasin; Mariam Mohamad; Zaliha Ismail; Zahir izuan Azhar (Malaysian Journal of Public Health Medicine, 2020)
As cognition declines with age, cognitive impairment rates are expected to increase ranging from 100% to 300% in this region. It could be higher among elderly who had any chronic diseases. The aim of the present work was to determine the prevalence and associated factors of cognitive impairment among elderly with hypertension. A clinic-based, cross-sectional study was conducted at several community clinics in Sabak Bernam and Hilir Perak districts from July to December 2015. A total of 480 patients were recruited. The prevalence of cognitive impairment was 13.13% (95%CI: 13.11, 13.15). Factors associated with cognitive impairment among elderly hypertensive were no formal educational level [OR: 3.95 (95%CI: 1.80, 8.67)]; history of high cholesterol [OR: 3.24 (95%CI: 1.15, 9.16)]; underweight [adj. OR: 4.88 (95%CI: 1.34, 17.67)]; and increasing age [OR: 1.03 (95%CI: 1.01, 1.06)]. Public health policy makers and geriatric practitioners should emphasise on early cognitive function assessment among elderlies who are hypertensive, unemployed, poor educational background, males, high cholesterol level and underweight to enhance the quality of geriatric services. Earlier establishment of diagnosis may prevent from greater rate of decline in cognitive functioning among this vulnerable group.